A novel peak shaving algorithm for islanded microgrid using battery energy storage system - Uddin, Moslem; Romlie, M.F.; Abdullah, M.F.; Tan, Chia Kwang; Shafiullah, G.M.; Bakar, Ab Halim Abu (Elsevier, 2020)
The objective of this study is to propose a decision-tree-based peak shaving algorithm for islanded microgrid. The proposed algorithm helps an islanded microgrid to operate its generation units efficiently. Effectiveness of the proposed algorithm was tested with a BESS-based MATLAB/Simulink model of an actual microgrid under realistic load conditions which were recorded. To evaluate the performance, simulation case studies were conducted under various load conditions and results were compared with conventional techniques. Results showed that the proposed algorithm offers a simple and effective way of peak load shaving without heavy computational burdens often needed in other methods. The comparison analysis verified that the proposed algorithm can effectively mitigate the peak load demand regardless of the schedule of the generators, where conventional methods were limited. The financial benefit investigation shows that microgrid utility can enjoy substantial savings, while reducing of the peak demand of the microgrid. Thus, the islanded microgrid that include fuel-based generation can implement the proposed technique to reduce the consumption of fuel and increase the efficiency of fuel-based generation through peak load mitigation. © 2020 Elsevier Ltd